Marked for revenge - Hansen, Valerie (Love inspired suspense., 2019)
EMT Kaitlin North can't believe ithe shooting victim at an isolated Ozark cabin is the man who once saved her life. Now the only way she can keep undercover police officer Daniel Ryan alive is to help him elude the hitman on his trail. With danger closing in, Kaitlin and Ryan need to trust each other's instincts.